19 Prevalence and Characteristics of Patients with Intradialytic Hypertension in Indonesia. (November 2017) - Japar, Karunia Valeriani; Vatvani, Akhil Deepak; Waren, Kalis; Wibisono, Prio; Alferinda, Karlina; Lemuel, Theo Audi Yanto
Abstract : Background: Intradialytic hypertension (IDH) is common and it increases the incidence of cardiovascular morbidity and mortality, however this is often ignored. The pathophysiological mechanisms are still unclear. Little is known about the demographic, clinical and laboratory characteristics. Objective: The aim of this study is to identify the prevalence of IDH and compare the clinical characteristics of patients with and without IDH. Methods: This is a multicenter cross sectional study that took place in 3 hemodialysis clinics. We compared characteristics such as age, BMI, duration of hemodialysis, hemoglobin, hematocrit, ureum, creatinine, sodium, potassium, calcium, uric acid, ferritin, erythrocyte, iron, total cholesterol, MAP and dry body weight in patients with IDH and control group without IDH. IDH was defined as >10 mmHg increase in systolic BP in atleast four of six prior consecutive hemodialysis sessions. Analysis was done using T-test or Mann-Whitney, depending on the distribution of data. Results: Out of 114 patients, 86(62.3%) were male. IDH was present in 47(34.1%) patients. The mean age in IDH and control group were 53.4(±13.2) and 52.8(±12.4) years respectively ( p : 0.800). The mean BMI of IDH and control group were 21.8(±3.7) and 24.0(±4.4) kg/m 2 respectively ( p : 0.031). The meanMAP during dialysis of IDH and control group were 108(±13.1) and 98.6(±23.2) mmHg respectively ( p : 0.011). The median creatinine levels of IDH and control group were 8.1(3.02–22.20) mg/dl and 10.8(2.89–22.0) mg/dl respectively ( p: 0.008). Other variables did not have any significant difference between the 2 groups. Conclusion: The prevalence of IDH ishigher than previously reported. Patients with IDH have lower BMI, higher MAP and lower creatinine levels than in controls.